Potential Economic Value of Water Resource Sustainability for Sustainable Environment: A Case Study in South Sumatra, Indonesia - Juniah, Restu; Toha, M. Taufik; Zakir, Syaifudin; Rahmi, Hisni (International Journal on Advanced Science, Engineering and Information Technology, 2023)
Erosion in coal mining land causes water quantity and quality depletion and inadequate drinking water resources for surrounding communities, making water resources unsustainable. Meanwhile, reclamation reduces erosion but cannot restore water depletion optimally; thus, these resources remain unsustainable. These resources remain unsustainable. The objectives of this study were to develop a water resource sustainability concept for a sustainable environment by analyzing the potential economic value and, secondly, to calculate the water resource value due to erosion, reclamation, and domestic and economic importance, of recycling efforts. The method used in this study was the Expanded NPV. Furthermore, the total potential economic value of water resources loss resulting in unsustainability was IDR 1,137,621,671,375 or IDR 1.14 trillion. In contrast, the potential economic value of depleted water utilization for drinking was IDR 2,298,339,797,000 or IDR 2.3 trillion. Therefore, this utilization provides a potential economic value worth IDR 1.16 trillion for the resources’ sustainability in the TAL area of PTBA. The study found and recommended depleted water utilization for drinking as a suitable method to replace water resources lost due to erosion and community drinking water resource loss and to discover a sustainable environment’s sustainability concept. In addition, the study formulates environmental economics as a new mining science related to natural resource economics and mining for sustainable water resources and the mining environment.